Experimental study of solar chimney power plant - Haythem Nasraoui; Zied Driss; Hedi Kchaou (University of Eloued, 2019)
Solar chimney power plants are passive thermal systems that use greenhouse effect to produce electricity from the solar radiations. The performance of these devices vary from one climate to another. Indeed, the building site of the SCPP is a special parameter for its total effectiveness. The aim of this work was to present an experimental investigation of a solar chimney prototype under the climatic conditions of Sfax, Tunisia. In fact, Sfax is characterized by its arid and sunny climate. The impact of the climatic conditions of Sfax city on the aero-thermal characteristics of the considered prototype is carried out. The present outcomes show that the solar chimney power plant is an applicable device in Tunisian region Sfax.
Intervention
Keywords: Renewable energy; Solar radiation; Chimney; Airflow